Peran Manajemen SDM terhadap Kinerja Karyawan pada Perusahaan Konstruksi PT. Marisa Jaya Abadi - Salsha Nabila Rahmadani; Heriyanto Heriyanto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The purpose of this study is to evaluate the role of human resource (HR) management in improving employee performance at PT Marisa Jaya Abadi, a construction company that faces various problems with HR management. This research is also motivated by the importance of HR quality to achieve company goals and project success, as well as the need to evaluate existing HR management policies and practices. This research utilizes an independent study approach which allows the researcher to expect that the results of the research will provide practical advice on how to improve the effectiveness of human resource management in business and provide information to other construction companies. Consequently, this research enhances academic knowledge of HR management and helps the construction industry by improving employee productivity and satisfaction.